On applicability of Bayes' formula - Alexander I. Dolgov (Advanced Engineering Research)
Bayes' formula is the research subject. The work objective is to analyze the formula application and widen the scope of its applicability. The first-priority problem includes the identification of the Bayes' formula disadvantages based on the study of the relevant publications leading to incorrect results. The next task is to construct the Bayes' formula modifications to provide an accounting of various single indications to obtain correct results. And finally, the incorrect results obtained with the application of Bayes' formula are compared to the correct results calculated with the use of the proposed formula modifications by the example of the specific initial data. Two methods are used in studies. First, the analysis of the principles of constructing the known expressions used to record the Bayesian formula and its modifications is conducted. Secondly, a comparative evaluation of the results (including the quantitative one) is performed. The proposed modifications provide a wider application of Bayes' formula both in theory and practice including the solution of the applied problems.